Continuous Midwifery Care (Continuity Of Care) For A Pregnant Woman With Grade Ii Hyperemesis Gravidarum: A Case Study At An Independent Midwifery Practice In Medan Amplas, North Sumatra, Indonesia, 2026 - Abel Amanda; Rosmani Sinaga; Ribur Sinaga; Kamelia Sinaga; Juniarsih Juniarsih (Universitas Pahlawan Tuanku Tambusai, 2026)
Hyperemesis gravidarum is characterized by severe and persistent nausea and vomiting during pregnancy, which may lead to fluid and electrolyte imbalance and adversely affect maternal and fetal health if not managed appropriately. Continuity of Midwifery Care (CoMC) is a comprehensive and continuous care approach that aims to ensure optimal maternal and neonatal health outcomes throughout pregnancy, childbirth, the postpartum period, neonatal care, and family planning. Objective this case study aimed to implement Continuity of Midwifery Care for a pregnant woman with Grade II hyperemesis gravidarum at an independent midwifery practice in Medan Amplas, North Sumatra, Indonesia. Methods a descriptive case study design was employed using Helen Varney’s seven-step midwifery management approach and SOAP documentation. Data were collected through interviews, direct observation, physical examination, and review of clinical documentation. Results the participant was a 22-year-old primigravida (G1P0A0) at 26 weeks of gestation who presented with excessive nausea and vomiting occurring approximately eight times daily, accompanied by weakness, dizziness, weight loss, hypotension (90/70 mmHg), sunken eyes, and pale lips. These clinical findings supported the diagnosis of Grade II hyperemesis gravidarum. Continuous midwifery care, including comprehensive assessment, health education, nutritional counseling, symptom management, and regular follow-up, resulted in improvement of maternal condition throughout pregnancy and continuity of care until the postpartum and family planning periods. Conclusion the implementation of Continuity of Midwifery Care effectively improved maternal monitoring and the quality of healthcare services for women with Grade II hyperemesis gravidarum. This approach facilitated comprehensive, continuous, and individualized care throughout the maternal continuum. ring pregnancy, which may lead to fluid and electrolyte imbalance and adversely affect maternal and fetal health if not managed appropriately. Continuity of Midwifery Care (CoMC) is a comprehensive and continuous care approach that aims to ensure optimal maternal and neonatal health outcomes throughout pregnancy, childbirth, the postpartum period, neonatal care, and family planning. Objective: This case study aimed to implement Continuity of Midwifery Care for a pregnant woman with Grade II hyperemesis gravidarum at an independent midwifery practice in Medan Amplas, North Sumatra, Indonesia. Methods: A descriptive case study design was employed using Helen Varney’s seven-step midwifery management approach and SOAP documentation. Data were collected through interviews, direct observation, physical examination, and review of clinical documentation. Results: The participant was a 22-year-old primigravida (G1P0A0) at 26 weeks of gestation who presented with excessive nausea and vomiting occurring approximately eight times daily, accompanied by weakness, dizziness, weight loss, hypotension (90/70 mmHg), sunken eyes, and pale lips. These clinical findings supported the diagnosis of Grade II hyperemesis gravidarum. Continuous midwifery care, including comprehensive assessment, health education, nutritional counseling, symptom management, and regular follow-up, resulted in improvement of maternal condition throughout pregnancy and continuity of care until the postpartum and family planning periods. Conclusion: The implementation of Continuity of Midwifery Care effectively improved maternal monitoring and the quality of healthcare services for women with Grade II hyperemesis gravidarum. This approach facilitated comprehensive, continuous, and individualized care throughout the maternal continuum.